2018
DOI: 10.1111/andr.12523
|View full text |Cite
|
Sign up to set email alerts
|

Compartments with predominant ephrin‐B1 and EphB2/B4 expression are present alternately along the excurrent duct system in the adult mouse testis and epididymis

Abstract: Overall, this study represents the first analysis of EphB receptor and ephrin-B ligand expression in the normal adult testis and epididymis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Activin signaling (INHBB-ACVR2A/1B/2B) can influence germ cell development through the phosphorylation of SMAD2/3(58). EphB/ephrin-B signaling (EFNB1/2-EPHB4/6) may modulate spermatogenesis and spermiation ( 59 ). Further analysis of the TFs downstream of these intercellular communications revealed that most of these TFs were related to spermatogenesis (see Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activin signaling (INHBB-ACVR2A/1B/2B) can influence germ cell development through the phosphorylation of SMAD2/3(58). EphB/ephrin-B signaling (EFNB1/2-EPHB4/6) may modulate spermatogenesis and spermiation ( 59 ). Further analysis of the TFs downstream of these intercellular communications revealed that most of these TFs were related to spermatogenesis (see Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…A case study on human testicular cells indicated prominent signal crosstalk between ST cells and SSCs. Most of the inferred intercellular communications (41/47) from ST cells to SSCs have been implicated in spermatogenesis or SSC differentiation ( 53 , 54 , 56 , 58 , 59 ), and some of them were confirmed by immunofluorescence assays. Intercellular communication analysis also indicated that intercellular crosstalk among germ cells may play roles in spermatogenesis, and a communication axis from P to SSCs (GDF5-BMPR1B-SMAD1) was confirmed by immunostaining.…”
Section: Discussionmentioning
confidence: 95%
“…This segment pair revealed that the upregulated DEGs may play important roles in toxicant detection and sperm maturation; Taste 2 Receptor Member 42 (TASR42), Epididymal Protein 3A (EDDM3A), testisin (PRSS21) (Governini et al, 2020;Kirchhoff et al, 1998;Netzel-Arnett et al, 2009), transcription factor (Paired Box 2, PAX2) (Lowen et al, 2001), and restructuring of sperm head plasma membrane, which is a form of prominent maturational changes (Sulfhydryl oxidase 1, QSOX1) (Wang et al, 2018). EPHB6 acts as sensor for unidentified chemicals and also participates in cell adhesion as well as sperm transport (Gofur & Ogawa, 2019) F I G U R E 5 Gene Ontology (GO) categories of all genes and differentially expressed genes (DEGs) of cattleyak epididymis. The number and percentage of genes in biological process, cellular component, and molecular function are indicated for all genes and DEGs, respectively.…”
Section: Caput Versus Corpusmentioning
confidence: 99%
“…This review aims to illustrate the potential for developing targeted vehicles, targeting methods, and therapeutic cargo to modulate Eph/ephrin signaling (Figure 2). Pharmaceuticals 2020, 13, x FOR PEER REVIEW 3 of 18 disorders [4,5,9], musculoskeletal growth and metabolism diseases [42][43][44][45], ischemic tissue injury [46][47][48][49][50][51][52][53][54][55][56] and malignancies [7,57,58], reproductive/fertility illnesses [59][60][61][62] and organ fibrosis [10,63].…”
Section: Eph/ephrin Is a Ubiquitous Therapeutic Targetmentioning
confidence: 99%